Analysis of risk factors for incomplete inpatient medical records using the fishbone method - Ernawati, Ernawati; Novratilova, Sinta (Institute of Computer Science (IOCS), 2025)
Incomplete inpatient medical summaries remain a persistent issue that affects administrative processes and the quality of patient data. This study aimed to analyze the completeness and contributing factors of incomplete inpatient medical summaries using the Fishbone Method (Ishikawa Diagram). A qualitative descriptive approach was employed, with data collected through observations, interviews, and document reviews of 99 inpatient medical summaries, selected using Slovin’s formula with a 10% margin of error. The study involved medical record officers and healthcare professionals, selected through purposive sampling. Data analysis followed the qualitative descriptive method, including data reduction, data presentation, conclusion drawing, and triangulation. The findings identified five primary factors contributing to incomplete medical summaries: Man (low compliance among healthcare professionals), Method (suboptimal Standard Operating Procedures), Machine (ineffective hospital information systems), Money (insufficient investment in training), and Material (medical records not yet fully electronic). The study recommends medical staff training, SOP optimization, and the implementation of an electronic medical record system with a required lock feature to ensure complete documentation of inpatient medical summaries.